The role of preferences and opportunity costs in determining the time allocated to housework - Leslie S. Stratton (Institute for the Study of Labor (IZA), 2012)
The time devoted to housework in couple households is substantial. Research on intrahousehold time allocations has generally assumed that housework is a necessary evil and that the partner with the lower opportunity cost of time in the market will devote more time to home production. In reality, households/individuals are likely motivated to maximize happiness, and preferences regarding even mundane household chores differ considerably. We use information on preferences, opportunity costs, and time use from the 2000-2001 United Kingdom Time Use Survey to examine the time partners spend doing laundry, ironing, cleaning, and food shopping. While compared with other household chores such as gardening and do-it-yourself repairs, the selected activities are generally less enjoyable, preferences do vary across the population and are correlated with reported time use. Joint multivariate analysis of his and her time on weekend and weekday days as well as maid service reveals that her opportunity cost of time matters substantially more than his, but that his preferences play a greater role than hers.
urn:nbn:de:101:1-201207125693
Keywords: D13; J22; 330; time allocation; housework; preferences; Hausarbeit; Zeitverwendung; Ehe; Frauen; Opportunitätskosten; Männer; Präferenztheorie; Schätzung; Großbritannien